Preparation of three-layered porous PLA/PEG scaffold: relationship between morphology, mechanical behavior and cell permeability. (February 2016) - Scaffaro, R.; Lopresti, F.; Botta, L.; Rigogliuso, S.; Ghersi, G.
Abstract: Interface tissue engineering (ITE) is used to repair or regenerate interface living tissue such as for instance bone and cartilage. This kind of tissues present natural different properties from a biological and mechanical point of view. With the aim to imitating the natural gradient occurring in the bone–cartilage tissue, several technologies and methods have been proposed over recent years in order to develop polymeric functionally graded scaffolds (FGS). In this study three-layered scaffolds with a pore size gradient were developed by melt mixing polylactic acid (PLA) and two water-soluble porogen agents: sodium chloride (NaCl) and polyethylene glycol (PEG). Pore dimensions were controlled by NaCl granulometry while PEG solvation created a micropores network within the devices. Scaffolds were characterized from a morphological and mechanical point of view in order to find a correlation between the preparation method, the pore architecture and compressive mechanical behavior. Biological tests were also performed in order to study the effect of pore size gradient on the permeation of different cell lines in co-culture. To imitate the physiological work condition, compressive tests were also performed in phosphate buffered saline (PBS) solution at 37 °C. The presented preparation method permitted to prepare three-layered scaffolds with high control of porosity and pore size distribution. Furthermore mechanical behaviors were found to be strongly affected by pore architecture of tested devices as well as the permeation of osteoblast and fibroblast in-vitro .